Padrões sazonais da variabilidade interanual da precipitação sobre a América do sul associadas às componentes enos e não-enos: impacto na vazão da bacia do Paraná - Souza, Itamara Parente de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2018)
The anomalous seasonal patterns of interannual rainfall variability over South America (SA) and its impact on rivers in the Paraná basin associated with El Niño-Southern Oscillation (ENSO) and non-ENSO (residual) components were evaluated during the 1970-2013 period. Seasonal patterns were derived from the Empirical Orthogonal Functions (EOF) analyzes applied to the series of total and residual precipitation anomalies and are referred to here as total (TOT) and residual (RES) patterns, while the associated patterns to the ENSO mode were obtained through the linear correlations between the NINO index and the precipitation anomalies on SA. In relation to the EOF patterns, the winter and autumn seasons, the first mode is associated with variations occurring in the Tropical Atlantic while the component in ENOS is defined as secondary mode. Variations in the tropical Atlantic mainly affect precipitation in the region north and northeast of Brazil, while variations in the Southwest Atlantic are modulating the precipitation between central-east and southeast of SA. On the other hand, for the spring and summer seasons, the ENSO explains most of the variability of the dominant patterns. This relationship is mainly associated with precipitation in the north, northwest and south of SA. The dynamics of these relationships involve variations in Walker's circulation and in the Pacific/ North America (PNA) and Pacific/South America (PSA) teleconnections patterns. The results confirm that in years of ENSO precipitation signals are intensified in the southeast and north of the SA, but in the absence of ENSO, the extratropical teleconnections patterns weaken leading to the reduction of precipitation. The changes in the local SST of the South Atlantic mainly modulate the circulation near the east coast of the AS that generates a dipole between the center-east and southeast of Brazil. In addition, discharges from the Parana basin rivers responded to large-scale standards. In years of ENSO, flow rates are associated with the transport of South American Low Level Jets (SALLJ). On the other hand, the discharges associated to the non-ENSO component presented strong relations with transport from the South Atlantic. These results show the important role of local forcing for the precipitation on the east coast of the AS and for discharges of the rivers of an important basin of Brazil. In summary, the results presented in this study define the relative contribution of the components associated to ENOS and non-ENOS in the determination of the seasonal patterns of precipitation and discuss their impacts on the Paraná basin
Keywords: Precipitação; ENOS; não-ENOS